English English - Hasbullah, Hasbullah; Mustarih, Mutiara Mushafryane; Wibowo, Aryono Adi (AGUSPATI Research Institute, 2021)
Abstract: Micro, Small, and Medium Enterprises (SME) are the main pillars of the Indonesian economy because they have a strong foundation in driving the wheels of the national economy. Inventory is an essential factor in SME production costs to boost competitive advantage. Conventionally, Local SMEs in the pest control industry do not yet have a method or system of inventory control for pest control raw materials. This study tries to conduct in-depth research of local SMEs in the pest control industry to minimize the shortage of raw materials. An observation of this study found out that material shortage in local SME could happen every month that caused stop supply to customers. The objective of this paper proposes an appropriate and efficient stock of pest control material to improve the shortage problem. For achieving the research objective, the approach used a case study on Nuvaq material inventory in an SME in Jakarta, Indonesia.. The forecasting technique with minimal error is the Linear Regression method giving results with the smallest forecast errors. It can be seen from the smallest MAD, MAPE, SEE, and MSE. The economic order quantity is 100 Liter Nuvaq Material, reorder points can be made when the supply is 36 Liters, and safety stock for Nuvaq raw materials is 16 liters.